Corrective and maintenance phosphorus fertilization on sugarcane yield in Oxisols - Rein, Thomaz Adolpho; Santos Junior, João de Deus Gomes dos; Sousa, Djalma Martinhão Gomes de; Carvalho, Wellington Pereira de; Lemes, Gabriel de Castro (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate sugarcane (Saccharum spp.) yield in response to corrective and maintenance phosphorus fertilization in Oxisols. Two experiments were carried out in randomized complete blocks with four replicates. In the corrective fertilization treatments, 150 kg ha-1 P2O5 were broadcast and incorporated before planting. In the maintenance fertilization treatments, 40 kg ha-1 P2O5 per year were applied over the trash blanket. All treatments, except the control, were fertilized with 170 kg ha-1 P2O5 in the planting furrow. The first experiment was carried out in a sugarcane expansion area and the second, in a replanting area, in Oxisols with a low and high phosphorus availability, respectively. In the first experiment, corrective fertilization increased cane yield in 13.4 Mg ha-1 for plant cane and in 14.6 Mg ha-1 for the average of four ratoon crops, whereas maintenance fertilization increased yield in 17.7 and 8.1 Mg ha-1 for the average of four ratoon crops for the treatments without and with corrective fertilization, respectively. In the second experiment, there were no significant differences between treatments regarding yield. Corrective and maintenance phosphorus fertilization should be considered for sugarcane in areas where soil phosphorus availability is limiting.